Dual-template docking oriented molecular imprinting: a facile strategy for highly efficient imprinting within mesoporous materials1. Issue 54 (11th July 2015) - Chen, Yang; Li, Xinglin; Yin, Danyang; Li, Daojin; Bie, Zijun; Liu, Zhen
<x xml:space="preserve">Abstract</x> Molecular imprinting within mesoporous materials is a challenging task. Herein, we present a new strategy, called dual-template docking oriented molecular imprinting (DTD-OMI), for facile and highly efficient imprinting within mesoporous materials.